PENGARUH DANA ALOKASI KHUSUS (DAK) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA MODAL PADA PEMERINTAH KABUPATEN NAGAN RAYA TAHUN 2009-2013 - Surna Lastri (Jurnal Akuntansi Muhammadiyah (JAM), 2015)
This research was conducted at the Government Nagan Raya years 2009-2013 in order to test the effect of Special Allocation Funds and local revenues for capital expenditures.Â This study uses data obtained based on the financial statements of the Government of Nagan highway. Testing technique used is multiple linear regression analysis using the program Statistical Product and Service Solutions (SPSS) version 18. The test results showed that capital spending simultaneously influenced by the Special allocation funds and revenue. Special allocation of funds partially affect capital spending by demonstrating the positive direction, the higher allocation of Special Allocation Funds from the central government, the greater the capital expenditure spent. Similarly, the results of testing on revenue partially affecting the capital expenditure with the positive direction, the greater the local revenues realized Nagan Raya District Government, the greater the capital expenditure spent by the regional government.Keywords: Special Allocation Fund, Local Revenue and Capital Expenditure